Determining Risk Factors for the Development of Temporomandibular Disorders during Orthodontic Treatment - Alessandro Ugolini; Federico Garbarino; Luca Di Vece; Francesca Silvestrini-Biavati; Valentina Lanteri (Applied Sciences, 2020)
Temporomandibular disorders (TMD) represent a complex disease with a multifactorial etiology. Despite several studies on the subject, a causal relationship between orthodontic treatment and different forms of TMD has not been established. The aim of this study was to analyze the effect of orthodontic treatment on two aspects of TMD: myofascial pain and disc displacement. This retrospective cohort study followed 224 orthodontic adult patients at three points in time: before treatment (T0), immediately after treatment (T1), and one year after treatment (T2). Disc displacement and myofascial pain were evaluated through a clinical assessment and with a semi-structured interview, along with headache, neck, and shoulder pain parameters and behavioral and somatic accompanying symptoms. Multivariate logistic regression was used to identify risk factors that could influence the development of TMD in these patients. There was a non-significant increase in disc displacement during orthodontic treatment, which mostly resolved after completion of treatment. Myofascial pain scores worsened during treatment, but improved when compared with the baseline once treatment was complete (T0 = 51.3%, T1 = 64.6%, T2 = 44.9%). Female gender (aOR = 1.9, CI 95%, 1.23–2.36), the presence of somatic symptoms (aOR = 3.6, CI 95%, 2.01–5.84), and symptoms of anxiety or depression (aOR = 2.2, CI 95%, 1.14–4.51) were significant risk factors associated with the development of TMD. There is a low and not significant risk of TMD development during orthodontic treatment. When TMD occurred, they resolved within 1 year of the end of treatment.